Economic importance of the leafminer Liriomyza sativae (Diptero: Agromyzidae) as a pest of beans in the Valle del Cauca - CRUZ, MARIBEL; CARDONA, CÉSAR (Revista Colombiana de Entomología, 1998)
To evaluate the damage caused by the  leafminer Liriomyza sativae Blanchard in beans, four field trials were carried out. The population development of the insect with respect to the crop cycle was recorded, the percentage of parasitism by Diglyphus begini Ashmead was measured, and different leafminer control alternatives with effective and noneffective products, treatment with calendar applications similar to that used by the majority of farmers and control were compared. It was determined that the insect was present during most of the crop cycle and that the populations were variable depending on environmental conditions and the action of natural enemies. The ectoparasitoid D. begini established 17 days after planting, its activity was permanent, and parasitism levels were as high as 72.5%. There were no differences in yield obtained in the field. No clear economic advantage (cost/benefit) existed between chemical treatments with respect to the control. The similarity in economic benefits between farmer's practices and no control treatments demonstrated little or no importance of the leafminer, confirming that the perceptions of farmers with respect to leafminer damage are exaggerated and that repetitive use of insecticides against this insect is not justified.